The Role of ICG Angiography in Decision Making About Skin-Sparing in Pediatric Acute Trauma - Han, Tao; Sun, Buhao; Wang, Weidong; Cui, Jie; Shen, Weimin (Frontiers in Pediatrics, 2022)
Background: Indocyanine green (ICG) angiography has been proven useful in assessing skin flap perfusion in plastic and reconstructive surgeries. This research aimed to explore its role in decision-making about skin-sparing in children's acute trauma. Methods: A total of 19 cases suffering with acute trauma from January 2019 to September 2021 were retrospectively assessed. Both ICG angiography and clinical judgement were performed to evaluate skin tissue viability. The intraoperative decisions for each case depended on the specific condition of traumatic wound, including tissue perfusion, skin defect area and location of wound. Postoperative vascular imaging software was used to quantified the tissue perfusion, and the duration of postoperative follow-up was from 6 to 18 months. Results: Among them, 18 (94.7%) patients experienced treatments according to ICG angiography and did not develop postoperative necrosis. One case with right forearm trauma suffered from partial necrosis. Hypertrophic scar and local infection were the independent complications, which were managed by symptomatic treatment. Conclusion: ICG angiography may reduce the risk of postoperative necrosis, and renders a promising adjunctive technique for surgeons to make reasonable decision in skin-sparing in acute pediatric trauma.